UNSUR DAN MAKNA NAMA PAGUYUBAN SENI REYOG PONOROGO: IDENTITAS, ETNISITAS DAN STRATEGI PEMERTAHANAN BAHASA JAWA KUNO - Alip Sugianto (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2022)
Name is a social identity as an object marker, one of which is the naming of the Reyog Ponorogo community. As a traditional art, this art still maintains the use of the name with Old Javanese as one of the cultural identities of the Panaragan Javanese ethnicity. One of the reasons behind the use of this name is local wisdom as an effort to maintain the Old Javanese language. This study has several objectives: (1) to describe the elements behind the naming of the Reyog Ponorogo community (2) to describe the meaning contained in the Reyog Ponorogo community (3) what factors are behind the preservation of the Old Javanese language in the naming of the Reyog community. The data in the form of the names of the Reyog associations obtained from the Tourism Office were taken by purposive sampling and interviews and interpretation using a qualitative descriptive approach. The findings in this study contained several naming elements, namely elements of religion, nature, flora, fauna and other entities. This element reflects the meaning behind the name of the Reyog Ponorogo community and persists in the use of Old Javanese because of the attitude of the people who have a positive primodialism and ethnocentric attitude so that the name of the Old Javanese language still persists in the use of the name of the Reyog community.